Dukungan suami terhadap breastfeeding self-efficacy ibu dalam pemberian ASI eksklusif - Ramdhania, Desti; Simamora, Elfrida (Holistik Jurnal Kesehatan, 2025)
Background: Breast milk is a safe, clean food that contains energy and nutrients needed by babies. In the breastfeeding process, mothers need support, especially from their husbands, to improve their abilities. Purpose: To determine the relationship between husband's support and mothers' self-efficacy in providing exclusive breastfeeding. Method: This study used a cross-sectional design with a sample of 61 respondents obtained using a purposive sampling technique. The sample inclusion criteria were mothers who had babies aged 0-6 months and mothers who had partners living in the same house. The instruments used were a questionnaire on the partner's intention scale for breastfeeding and a short-form breastfeeding self-efficacy scale. Data analysis used the Fisher Exact test. Results: Most respondents were 20-29 years old, namely 34 respondents (55.7%), the last level of education of respondents was at secondary and higher education levels, namely 26 respondents (42.6%), most mothers did not work, namely 47 respondents (77%), and mothers were reported to be multiparous, namely 37 respondents (60.7%). The variable of respondents' husband's support is in the good category as many as 51 respondents (83.6%) and breastfeeding self-efficacy is in the moderate category as many as 34 respondents (55.7%). Based on the results of the Fisher Exact test, a sig. (2-tailed) value of 0.002 (<0.005) was obtained, meaning that there is a relationship between husband's support and mother's breastfeeding self-efficacy in providing exclusive breastfeeding. Conclusion: There is a significant relationship between husband's support and mother's breastfeeding self-efficacy in providing exclusive breastfeeding.   Keywords: Exclusive Breast Milk; Husband's Support; Mother's Self-Efficacy.   Pendahuluan: Air susu ibu (ASI) adalah makanan yang aman, bersih, dan mengandung energi serta nutrisi yang dibutuhkan bayi. Pada proses menyusui, ibu membutuhkan dukungan terutama dari suaminya untuk meningkatkan self-efficacy. Tujuan: Untuk mengetahui hubungan antara dukungan suami terhadap breastfeeding self-efficacy ibu dalam pemberian ASI eksklusif. Metode: Penelitian ini menggunakan desain cross-sectional dengan sampel sebanyak 61 responden yang didapatkan menggunakan teknik purposive sampling. Kriteria inklusi sampel yaitu ibu yang memiliki bayi 0-6 bulan dan ibu yang memiliki pasangan tinggal serumah. Instrumen yang digunakan adalah kuesioner partner breastfeeding intention scale dan breastfeeding self-efficacy scale short form. Analisis data menggunakan uji fisher exact. Hasil: Mayoritas responden berusia 20-29 tahun sebanyak 34 responden (55.7%),  tingkat pendidikan terakhir responden berada pada tingkat pendidikan menengah dan tinggi sebanyak 26 responden (42.6%), sebagian besar ibu tidak bekerja sebanyak 47 responden (77%), dan dilaporkan ibu dengan status multipara berjumlah 37 responden (60.7%). Variabel dukungan suami responden berada pada kategori baik sebanyak 51 responden (83.6%) dan breastfeeding self-efficacy sedang sebanyak 34 responden (55.7%). Berdasarkan hasil uji fisher exact diketahui nilai sig. (2-tailed) sebesar 0.002 (< 0.005), artinya terdapat hubungan dukungan suami terhadap breastfeeding self-efficacy ibu dalam pemberian ASI eksklusif. Simpulan: Terdapat hubungan yang signifikan antara dukungan suami terhadap breastfeeding self-efficacy ibu dalam pemberian ASI eksklusif.   Kata Kunci: Air Susu Ibu (ASI) Eksklusif; Breastfeeding Self-Efficacy Ibu; Dukungan Suami.